Cadmium accumulation and tolerance in the Cd‐accumulator Capsella bursa‐pastoris. Issue 3 (18th September 2014) - Liu, Yingjie; Lin, Lijin; Jin, Qian; Zhu, Xuemei
<x xml:space="preserve">Abstract</x> Advances in phytoremediation research require the selection of new hyperaccumulators or accumulators and investigations of their tolerance and accumulation of heavy metals. Two concentration gradient experiments (preliminary and verification), involving the same soil Cd concentrations (0, 25, 50, 75, 100, and 125 mg kg−1), were conducted to study Cd accumulation and tolerance in Capsella bursa‐pastoris. In the preliminary and verification concentration gradient experiments, the Cd content in shoots of C. bursa‐pastoris exceeded 100 mg kg−1 at a soil Cd concentration of 50 mg kg−1, and the maxima of Cd contents in shoots were 307.67 and 369.20 mg kg−1 at 125 mg kg−1 Cd in soil, respectively. The shoot bioconcentration factor of C. bursa‐pastoris was greater than 1, but the translocation factor was less than 1.0 in the preliminary and verification concentration gradient experiments. In the verification concentration gradient experiment, the malondialdehyde content and the activities of superoxide dismutase, peroxidase, and catalase increased compared with the control. Therefore, C. bursa‐pastoris is a Cd‐accumulator with strong tolerance to Cd, and could be used to remediate Cd‐contaminated farmland soil in winter. © 2014 American Institute of Chemical Engineers Environ Prog, 2014 34: 663–668, 2015